Execution of Parker Solar Probe's unprecedented flight to the Sun and early results. (February 2021) - Guo, Yanping; Thompson, Paul; Wirzburger, John; Pinkine, Nick; Bushman, Stewart; Goodson, Troy; Haw, Rob; Hudson, James; Jones, Drew; Kijewski, Seth; Lathrop, Brian; Lau, Eunice; et al.
Abstract: Parker Solar Probe (PSP) was launched on August 12, 2018, on its way to enter the solar corona and "touch" the Sun for the first time. We utilize enormous planetary gravity assists from 7 repeated Venus flybys via a V 7 GA trajectory in 24 solar orbits over 7 years, to get within 8.86 solar radii from the Sun's surface. The probe successfully entered the V 7 GA trajectory and made the first Venus flyby only 52 days after launch. Five weeks later it flew by the Sun at a perihelion distance of 0.166 AU and flyby speed of 95.3 km/s, setting new records as the closest craft to the Sun and the fastest human-made object. In this paper, the overall strategy, plan, process, and early flight results and performance for PSP's flight execution including in-flight trajectory control and re-optimization, orbit determination and navigation, and trajectory correction maneuvers are presented. The unique challenges and operation constraints we encountered in flying a solar mission are described. Highlights: Flying to the sun's corona in an innovative V 7 GA trajectory with 24 solar flybys. Unprecedented challenges and operation constraints in the sun's harsh environments. In-flight trajectory control, re-optimization, orbit determination, and navigation. Flight results of launch and first Venus gravity-assist flyby and solar encounters.